QT interval changes and reversibility of QT dispersion in patients with acute pancreatitis - Buğdacı, Mehmet Sait; Tüzün, Ali; Koca, Harun; Çavusoğlu, Turhan; Akyüz, Ümit; Şentürk, Hakan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: QT dispersion is a sign of heterogeneity of ventricular myocardial wall and is associated with cardiac mortality and morbidity. Data regarding with the persistence of QT interval changes in cases with acute pancreatitis (AP) that required clinical follow-up, are insufficient. Therefore, in this study, we aimed to evaluate the QT interval changes during attack and after remission of the disease, in cases with AP. Materials and Methods: The cases admitted to the Gastroenterohepatology Clinic with the diagnosis of AP were included into the study. Ranson’s score parameters, electrocardiography and echocardiography of all patients included into the study were evaluated. Electrocardiographic changes were evaluated two times, during attack and after remission of the disease. Results: A total of 134 subjects (F/M:54/80, 41/59%) diagnosed as AP were included into the study. Seventy two (54%) of the AP cases included into the study were biliary, 32 (24%) were alcohol dependant, 19 (14%) were idiopathic, 9 (7%) were hyperlipidemic and 2 (1%) were ERCP related cases. Mean age of the patents was 57.7±15 years old (range: 19-82 years old) and mean Ranson’s score was 3.8±1.9 (range: 1-7), according to the numerical scoring system. We compared QT interval changes during the attack and after the remission of AP and found significant increase in QT dispersion levels during acute attack of AP (p<0,001). Conclusion: The most common electrocardiographic changes in AP patients are QT interval changes including QT dispersion. QT dispersion which was emerged during the attack recovered after the remission of the disease.